Distinguishing ripe spelt from processed green spelt (Grünkern) grains: Methodological aspects and the case of early La Tène Hochdorf (Vaihingen a.d. Enz, Germany) - Berihuete-Azorín, Marian; Stika, Hans-Peter; Hallama, Moritz; Valamoti, Soultana Maria (Journal of archaeological science, 2020)
The practice of harvesting green grains is known worldwide and, although it implies a higher investment of labour than collecting them ripe, it presents some advantages such as the possibility to extend the harvest time or to secure one year's crop yield in case of, for instance, bad weather close to ripening. However, the presence of green-harvested cereals in archaeobotanical assemblages has so far never been studied. No previous work has been carried out on how charring affects the size of grains with different degrees of maturity or of immature grains that underwent different processing activities prior to charring. The main aim of the present study was to observe kernel morphology of modern ripe and unripe spelt (Triticum spelta L.) grains and apply the results to the archaeobotanical remains retrieved at the early La Tène site of Hochdorf (Vaihingen a. d. Enz, Germany), where an archaeobotanical assemblage of charred spelt grains, apparently in different stages of maturity, was found. In order to discriminate these two maturity stages within one cereal species, modern specimens of ripe spelt and Grünkern have been charred and compared. The results of this experiment have allowed us to confirm the coexistence of spelt grains in different degrees of maturity in the early La Tène Hochdorf assemblage. Similarly, ethnographical information on modern Grünkern production provided information on the details of the processing of unripe spelt and the human choices to produce it. •We revisited a spelt assemblage with 2 morphotypes from Iron Age site of Hochdorf.•Modern ripe and unripe grains from traditional Grünkern producers are investigated.•Recent and archaeological sub-populations show significant breadth differences.•This paper confirms the first archaeological identification of unripe spelt grain.